PROTEOMIC STUDY OF CARBAPENEM-RESISTANT K. PNEUMONIAE CLINICAL ISOLATES - SUBRAMANIYAN, VETRISELVI; DHANARAJ, SURESH (International Journal of Applied Pharmaceutics, 2022)
Objective: Now it's a worldwide issue that carbapenem resistance is spreading. This has made K. pneumoniae infections more difficult to treat. All Klebsiella pneumonia's proteins were examined in this study, which focused on the carbapenem-resistant bacteria's response to meropenem. Methods: Proteomics (MALDI-TOF) and bioinformatics methods were combined to answer the new enigma of resistance. Functional annotation, pathway enrichment and protein–protein interaction were some of the uses of this data. Both KEGG and STRING played an important role (PPI). Results: Proteins that help synthesise DNA and RNA, proteins that aid in carbapenem degradation, and proteins that aid energy and intermediate metabolism are all subdivided into two classes.007A Conclusion: Bacterial survival and meropenem resistance may have been aided by four overexpressed proteins and their partners. A new anti-resistance medication based on these proteins could help restrict the growth of "bad bugs."